Anthraquinones- A probe to enhance the photovoltaic properties of DSSCs - Jinchu I; Jyothi R; N Pandurangan; Sreelatha KS; Krishnashree Achuthan; Sreekala CO (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Natural dye sensitized solar cells are a promising class of photovoltaic cells with the capacity of generating green energy at low production cost since no expensive equipment is required in their fabrication. Photovoltaics are a precious technology in the hasty world where energy prices are goes on increasing within seconds. Researchers are focusing to facilitate for producing eco-friendly, low cost and more efficient dye sensitized solar cells. In the present work we discuss the comparative photovoltaic studies of Lawsone, a natural dye from henna plant and Alizarin, a natural dye from the root of madder for fabricating the Dye sensitized solar cells (DSSCs). The absorption spectrum of Lawsone and Alizarin is found to be shifted to the longer wavelength region after the complex formation. As a result there is a significant increase in short circuit current density and conversion efficiency. This result compares with the standard dye i.e. N719 dye.